Answer:
y=4x−11
Step 1: Flip the equation.
4x−11=y
Step 2: Add 11 to both sides.
4x−11+11=y+11
4x=y+11
Step 3: Divide both sides by 4.
=
![(y+11)/(4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/jdn4c7foyekwcrlcrdm4zbptlbr615i2a1.png)
x=
+
![(11)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6ghpwp1ihj7qf78ls6rjzo105x27qwbusr.png)
y=-8x + 13
Step 1: Flip the equation.
−8x+13=y
Step 2: Add -13 to both sides.
−8x+13+−13=y+−13
−8x=y−13
Step 3: Divide both sides by -8.
=
![(y- 13)/(-8)](https://img.qammunity.org/2021/formulas/mathematics/high-school/1elorwpwc1kkodn7hrjjdd3mnx77pkrbo2.png)
x=
+
![(13)/(8)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mj3g2k5xwrjjax45g8knwfbe3b00x5ggjy.png)